Перспективи розвитку форми Української держави в процесі конституційної модернізації - Толстенко, Володимир Леонідович (My University, 2014)
Досліджено перспективи розвитку форми Української держави в процесі конституційної модернізації та діяльності Конституційної Асамблеї. Особлива увага надається правовому забезпеченню демократизму державно-правового режиму, верховенства права і законності. The prospects for the development of the form of the Ukrainian state in the process of constitutional modernization and the activities of the Constitutional Assembly are investigated. Special attention is paid to the legal support of the democracy of the state-legal regime, the rule of law and legality.
Keywords: держава; state; українська держава; the Ukrainian state; модернізація; modernization